Dimensions of Constitutional Rights in Enhancing Village Apparatus Awareness - Mamonto, Moch Andry Wikra Wardhana; Ramadan, Rizki; Buana, Andika Prawira (Advances in Community Services Research, 2025)
Purpose: This study aims to enhance constitutional awareness among the community of Kapita Village, Jeneponto Regency, by strengthening their understanding of constitutional rights as outlined in the 1945 Constitution of the Republic of Indonesia. Citizens' low awareness of their rights and role in overseeing government actions necessitates structured legal counseling. The objective is to provide citizens with fundamental knowledge of the constitution and foster a sense of legal awareness to ensure active participation in governance. Research Design and Methodology: This study employs a qualitative approach through direct legal counseling sessions. The counseling is delivered using an oral presentation method, incorporating simple and accessible language. A question-and-answer format is used to engage participants and encourage active discussion. Additionally, visual materials such as posters featuring statements from prominent figures about the Constitution, accompanied by illustrative images, are utilized to capture public attention and reinforce key messages. Findings and Discussion: Implementing this program resulted in an increased general understanding among participants regarding the function of the constitution and its role in governance. Citizens recognized the constitution as the supreme law of the land and an agreement between the state and its citizens. Moreover, they gained insight into their constitutional rights, particularly those directly impacting their daily lives, such as education, healthcare, and civic participation. Implications: The findings suggest that structured constitutional counseling can effectively promote legal awareness at the village level. Improved constitutional understanding can lead to more informed and active citizens participating in governance and advocating for their rights. The study highlights the importance of continuous legal education and engaging educational media to foster constitutional awareness in rural communities.